Development of a framework for services recovery for service industries - Kumar, Niriender; Md Isa, Filzah; Cheng, Wei Hin; Abdullah, Haim Hilman (Inderscience Publishers, 2012)
Service recovery refers to the actions a supplier takes in order to seek out dissatisfaction and as a response to poor service quality.The understanding of nature and determinants of service recovery performance in service industries is necessary in developing and implementing service recovery programmes especially in the service industry which requires a lot of human interaction.The objectives of this research are to develop a framework for services recovery performance for service industries based on the previous literatures.The study identified three main factors, namely organisational, personal and human resource, that affect the service recovery performance.This study provides added knowledge and insights into the factors that affect service recovery performance in general in service industries in the Malaysian context.